Combining acetabular and femoral morphology improves our understanding of the down syndrome hip. (October 2018) - Bakouny, Ziad; Assi, Ayman; Yared, Fares; Khalil, Nour; Mansour, Elie; Yaacoub, Jean Jacques; Skalli, Wafa; Ghanem, Ismat
Abstract: Background: Hip instability is frequent in patients with Down syndrome. Recent studies have suggested that skeletal hip alterations are responsible for this instability; however, there are currently no studies simultaneously assessing femoral and acetabular anatomy in subjects with Down syndrome in the standing position. The aim was to analyze the three-dimensional anatomy of the Down syndrome hip in standing position. Methods: Down syndrome subjects were age and sex-matched to asymptomatic controls. All subjects underwent full body biplanar X-rays with three-dimensional reconstructions of their pelvises and lower limbs. Parameter means and distributions were compared between the two groups. Findings: Forty-one Down syndrome and 41 control subjects were recruited. Acetabular abduction (mean = 52° [SD = 9°] vs. mean = 56° [SD = 8°]) and anteversion (mean = 14° [SD = 8°] vs. mean = 17.5° [SD = 5°]) as well as posterior acetabular sector angle (mean = 91° [SD = 7°] vs. mean = 94° [SD = 7°]) were significantly lower in Down syndrome subjects compared to controls (P < 0.01). Anterior acetabular sector angle (mean = 62° [SD = 10°] vs. mean = 59° [SD = 7°]; P < 0.01) was significantly higher in Down syndrome compared to controls. The distributions of acetabular anteversion (P = 0.002;V = 0.325), femoral anteversion (P = 0.004;V = 0.309) and the instability index (P < 0.001;V = 0.383) were significantly different between the two groups, with subjects with Down syndrome having both increased anteversion and retroversion for each of these parameters. Interpretation: Subjects with Down syndrome were found to have a significantly altered and more heterogeneous anatomy of their proximal hips compared to controls. This heterogeneity suggests that treatment strategies of hip instability in Down syndrome should be subject-specific and should rely on the understanding of the underlying three-dimensional anatomy of each patient. Highlights: Understanding hip instability in Down syndrome in 3D while standing is lacking. Down syndrome & control subjects had 3D EOS reconstructions of pelvis & lower limbs. Subjects with Down syndrome have altered and heterogeneous anatomy of proximal hips. Treatment strategies of hip instability in Down syndrome should be subject-specific.